1998
DOI: 10.1177/00030651980460031301
|View full text |Cite
|
Sign up to set email alerts
|

An Application of the Concept of the Therapeutic Alliance To Sadomasochistic Pathology

Abstract: This paper traces the history of the therapeutic alliance concept, examining how it has been used and misused, at times elevated to a central position and at others rejected altogether. The loss of this concept created a vacuum in classical psychoanalysis that has been filled by rival theories. The continuing usefulness of looking at the treatment process through the lens of the therapeutic alliance, particularly in relation to the manifold difficulties of working with sadomasochistic pathology, is suggested. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…As we have seen, there is signifi cant evidence (Connors, 2006 ;Johnson, 1999 ;Kaplan and Garfi nkel, 1999;Novick & Novick, 1998 ;Roth & Fonagy, 1996 ;Zerbe, 2008 ) a mixture of symptom-focused, cognitive behavioral, supportive, insight-oriented, affect-regulatory, medical and psychopharmacological interventions is often more helpful with a variety of clients than a single, linear approach. Much of this same research has shown that work with a team in which different specialties are provided by different therapists-e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As we have seen, there is signifi cant evidence (Connors, 2006 ;Johnson, 1999 ;Kaplan and Garfi nkel, 1999;Novick & Novick, 1998 ;Roth & Fonagy, 1996 ;Zerbe, 2008 ) a mixture of symptom-focused, cognitive behavioral, supportive, insight-oriented, affect-regulatory, medical and psychopharmacological interventions is often more helpful with a variety of clients than a single, linear approach. Much of this same research has shown that work with a team in which different specialties are provided by different therapists-e.g.…”
Section: Resultsmentioning
confidence: 99%
“…While some clients fi nd it useful, others fi nd it disturbing and/or distracting from the "real" work of therapy. Novick and Novick ( 1998 ) caution against confusing a professional alliance, which has specifi c therapeutic goals, with a more general, personal relationship. Yet a therapeutic relationship is also an interaction between two people that can make both members of a therapeutic dyad feel vulnerable (see Gabbard & Lester, 1995 ).…”
Section: Taking It Personallymentioning
confidence: 99%
See 2 more Smart Citations
“…Meissner's (1996) unequivocal position about analysis under any condition is instructive: "Unless the patient freely chooses to enter the analytic process and willingly engages in it, there is no possibility of a sound therapeutic alliance" (p. 194). In all cases, but perhaps especially in the training situation, establishing a therapeutic alliance is an ongoing, evolving process requiring specific therapist-patient negotiations and interaction forms related to the requirements of the analytic situation and work and to the engagement capacity of each person (see also Novick and Novick, 1998). Even Thomä and Kächele (1999), who "[pled] for a complete disconnection of the personal analysis from the main body of the psychoanalytic education," also held that "it is indispensable for an analytic therapist to experience for himself/herself the effects of unconscious processes on transferences and defenses in an intersubjective exchange" (p. 34).…”
mentioning
confidence: 99%